Comprehensive identification of bHLH transcription factors in Litsea cubeba reveals candidate gene involved in the monoterpene biosynthesis pathway - Yang, Jiahui; Chen, Yicun; Gao, Ming; Wu, Liwen; Xiong, Shifa; Wang, Siqi; Gao, Jing; Zhao, Yunxiao; Wang, Yangdong (Frontiers in Plant Science, 2022)
The basic helix-loop-helix (bHLH) family is a transcription factor superfamily comprising a substantial number of members that not only regulate terpenoid biosynthesis but participate in various metabolic processes in plants. Litsea cubeba is a representative woody oil tree species rich in terpenoids. However, the bHLH transcription factors were not identified of L. cubeba. In this study, we identified 173 bHLH genes from L. cubeba and divided these into 26 subfamilies based on phylogenetic analysis. The majority of bHLHs in each subfamily shared comparable structures and motifs. While LcbHLHs were unevenly distributed across 12 chromosomes, 10 tandem repeats were discovered. Expression profiles of bHLH genes in different tissues demonstrated that LcbHLH78 is a potential candidate gene for regulating monoterpene biosynthesis. LcbHLH78 and the terpene synthase LcTPS42 showed comparable expression patterns in various tissues and fruit development stages of L. cubeba. Subcellular localization analysis revealed that LcbHLH78 protein localizes to the nucleus, consistent with a transcription factor function. Importantly, transient overexpression of LcbHLH78 increased geraniol and linalol contents. Our research demonstrates that LcbHLH78 enhances terpenoid biosynthesis. This finding will be beneficial for improving the quality of L. cubeba and provides helpful insights for further research into the control mechanism of LcbHLH genes over terpenoid biosynthesis.